Impact of ovarian fetal tissue xenotransplantation associated with in vitro embryo production in annual genetic gain estimates for cattle weight traits (Veterinária Notícias, 2020)
Weighing and genealogy data of 1667 Brahman cattle were used to estimate the annual direct genetic gain for birth weight, weight at 120 days, 210 days and at 550 days of age. The annual genetic gain depends directly on the selection intensity, heritability and phenotypic standard deviation and inversely on the generation interval. It was considered five different generation intervals: 0.66 years (eight fetal months, considering fetal ovarian tissue xenotransplantation), 3.75 years (three years of life plus nine months of fetal life), 5.75 years, 7.75 years and 10.75 years. The genetic parameters were obtained by animal model, via Bayesian inference, using Monte Carlo Methods via Markov Chains. The estimate of annual genetic gain for all the traits evaluated was higher when considering the generation interval using fetal ovarian tissue xenotransplantation and lower when using 10.75 years. The fetal ovarian tissue xenotransplantation associated with in vitro embryo production, by reducing the generation interval, increases the annual direct genetic gain for weight traits, a fundamental situation for the animal breeding of the herds.